Doctor to the Resistance : The Heroic True Story of an American Surgeon and His Family in Occupied Paris - Vaughan, Hal, 1928-2013 (Book collections on Project MUSE., 2004)
"The Jackson story is a tale of self-sacrifice under unimaginable conditions, of danger, privation, arrest, and slavery. Doctor to the Resistance is a celebration of American patriotism and valor, and of Franco-American friendship."--Jacket.